Systematic review: Surfactant protein-D, diabetes mellitus, oxidative stress, infections and inflammation on the crossroad - Shireen Jawed; Mohamed, Mahaneem; Altaf, Benash; Wan Ghazali, Wan Syaheedah (Journal of the Pakistan Medical Association, 2024)
Objectives: To review the association of surfactant protein-D with type 2 diabetes mellitus, infections, oxidative stress and inflammation, and the changes in oxidative stress markers in type 2 diabetes mellitus. Method: The systematic review was conducted from April to September 2022, and comprised search on PubMed, Web of Sciences, Scopus, Science Direct and Google Scholar databases for relevant studies published in English language between January 1, 2000, and June 30, 2022. The search was updated in September 2022. After transferring literature to Mendeley, relevant data was extracted from the included studies. Quality assessment for eligible studies was done using Joanna Briggs Institute Critical Appraisal Checklist. Quality of evidences was assessed by using Grading of Recommendations Assessment, Development and Evaluation tool. Results: Of the 203 studies identified, 18(8.9%) were analysed; 16(89%) with humans and 2(11%) with animals as subjects There were 5 (31.25%) studies for SP-D, of which 4 (80%) studies reported lower surfactant protein-D in type 2 diabetes mellitus cases than controls. Its significant negative association with glycated haemoglobin was reported by 1(20%) study and 2(40%) studies with fasting blood glucose levels. Higher surfactant protein-D in type 2 diabetes mellitus cases and its positive association with glycated haemoglobin was reported by 1(20%) study. Recurrent infections were frequent in type 2 diabetes mellitus patients. Malondialdehyde level was higher and superoxide dismutase activity was lower in type 2 diabetes mellitus cases, reflecting oxidative stress. —Continue